Tourism Governance and the Influence of Stakeholder Networks - A Case Study from Western Australia - Pforr, Christof (Springer Gabler, 2015)
This study sets out to describe, analyse and explain the political processes which led to the Western Australian government’s decision to reject a proposed resort and marina complex at Maud’s Landing in the North West of Western Australia. The various interests in the Maud’s Landing development proposal are assessed in a policy network study which investigates if and how the key stakeholders, who contributed to or participated in the Maud’s Landing political process, worked together to shape the decision-making process.